PEGylated peptide-based imaging agents for targeted molecular imaging - Wu, Huizi; Huang, Jiaguo (Current protein & peptide science, 2016)
Molecular imaging is able to directly visualize targets and characterize cellular pathways - with a high signal/background ratio, which requires a sufficient...
Gesehen am 24.10.2019